Enhanced Photocatalytic Degradation Activity Using the V2O5/RGO Composite - Anuja A. Yadav; Yuvaraj M. Hunge; Seok-Won Kang; Akira Fujishima; Chiaki Terashima (Nanomaterials, 2023)
Semiconductor-based photocatalyst materials played an important role in the degradation of organic compounds in recent years. Photocatalysis is a simple, cost-effective, and environmentally friendly process for degrading organic compounds. In this work, vanadium pentoxide (V2O5) and V2O5/RGO (reduced graphene oxide) composite were synthesized by a hydrothermal method. The prepared samples were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), Raman spectroscopy, and UV-Vis spectroscopic analysis, etc. Raman analysis shows the occurrence of RGO characteristic peaks in the composite and different vibrational modes of V2O5. The band gap of flake-shaped V2O5 is reduced and its light absorption capacity is enhanced by making its composite with RGO. The photocatalytic degradation of methylene blue (MB) was studied using both V2O5 and V2O5/RGO composite photocatalyst materials. The V2O5/RGO composite exhibits a superior photocatalytic performance to V2O5. Both catalyst and light play an important role in the degradation process.